CRITICAL ANALYSIS IN HOSPITAL ADMINISTRATION IN THE MODERN ERA - EXAMINING CHALLENGES AND OPPORTUNITIES IN HEALTHCARE MANAGEMENT - 1Fahad Mesfer Ali Alqashanin, 2Muhammad Misfer Al-Qashanin, 3Misfer Saeed Mohammed Al-Qashanin, 4Farid JaberHadiLasloom, 5Hamad Salem Jaber Al Qawan, 6Muidh Farkhan Ali Alomar, 7MAJED MESFER FAHHAD Al Yami, 8Fahd Jaber HadiLasloom, (Chelonian Research Foundation, 2022)
Hospital administration today confronts a diverse array of challenges and opportunities driven by factors including technological innovations, shifting patient demographics, regulatory demands, and financial limitations. This article analyzes these challenges and their openings in healthcare administration. The methodology is clarified through a cautious survey of logical information, proofs, and proposals to advise restorative faculty. Much obliged to this inquiry, caregivers can learn about almost all changes within the treatment handle and make the vital strategies to address them. This combination permits inspectors to take advantage of open positions, decreasing competition and expanding the recognition of inspection and efficiency. Keywords: Hospital administration, healthcare management, challenges, opportunities, technological advancements, patient demographics, regulatory requirements, financial constraints.